A educação a distância e a formação continuada de professores de matemática: contribuições de um contexto formativo para a base de conhecimento docente - Pereira, Rudolph dos Santos Gomes [UNESP] (2015)
The results presented by the National Basic Education Evaluation System, by the International Program of Students Assessment, and by the High School National Exam indicate that Brazilian students have a low proficiency level in mathematics: they are able to perform basic mathematical operations and the reading and interpretation of simple graphs. These markers point to the need for changes in the Maths teaching and learning processes in the Basic Education which can be started with the teacher’s action, searching for alternatives to help him/her in the classroom activities. Taking that into consideration, this research aims at investigating the contributions given by Distance Learning, as a training context, in a Maths teacher continuing training course, with Mathematical Modeling activities, for the manifestation and development of knowledge and teaching knowledge. For the development of this research, the theoretical framework adopted was the one based on teacher training in the pedagogical alternative of the Mathematical Modeling, as well as the guidelines of the Distance Learning. The methodological procedures that guided the research were based on the concepts of qualitative research. In the course planning, tools offered by the Distance Learning process were considered for the communication between course takers and the researcher, material availability and activities performance. The implementation and development of the Continuing Training of Maths Teachers course at service in the Basic Education took place in the virtual learning environment known as Moodle. The course was offered in the distance mode, semi-distance learning, lasting a hundred hours, split in three modules in which modeling activities were performed. Six course takers took part in the project. The data collection was done by the following tools: chat, forum, daily logs and tasks (reflective memorials) where expressions and reflections by the course takers were registered during the length of the continuing training course. The Discursive Textual Analysis was adopted for the collected data analysis, which allowed for the interpretation and comprehension of the registrations made by the course takers. Hence, from the discursive textual analysis performed in the data considered in this doctoral dissertation, it was possible to conclude that distance learning, understood as a possible context for continuing teacher training, boosted the manifestation and development of knowledge and teaching knowledge, by the course takers who took part in the research, allowing, among other things, the development of the autonomy of these teachers by means of the activities proposed in the held course, leading them to look for solutions for the personal difficulties faced by each one of them.